Relation of Architectural Function and Form of Mosque Jami 'Al Mukarromah Kampung Bandan North Jakarta - Ashadi Ashadi; Anisa Anisa (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
There are two important aspects in architecture, namely function and form. Function is an activity that must be accommodated in an architectural form (space). This research was the exploration of function and form and the relation between them in architecture of Masjid Jami 'Al Mukarromah Kampung Bandan. The purpose of this research was to get the conclusion about the relation between activity in mosque and its architectural form. From the interpretation of this relation was expected to be revealed its meaning. This research used descriptive interpretive method. Field data collection was done by observing the activities in Masjid Jami 'Al Mukarromah and observing the architectural form of the mosque associated with the activities undertaken in the mosque. In addition to observation of the object of study, also conducted interviews with the main source who was direct descendants of Habib Abdurahman bin Alwi Asy-Syatiri named Habib Alwi bin Ali As-Syatiri. In addition, interviews were also conducted to marbot Masjid Jami 'Al Mukarromah Kampung Bandan. The results of this study showed two conditions: first, there was a relation between function and form, thus raising the meaning of functional architecture; secondly, there was no relation between function and form, especially with regard to the function of prayer and pilgrimages, whose containers (architectural forms) overlap, giving rise to syncretic architectural significance.